2020
DOI: 10.1088/1361-6501/ab7bc0
|View full text |Cite
|
Sign up to set email alerts
|

An error similarity-based error-compensation method for measurement in the nonuniform temperature field

Abstract: Measurement error compensation is a key issue for the application of laser trackers in an unsteady environment, especially in the nonuniform temperature field. Aimed at reducing induced measurement uncertainty, a measurement error compensation method with error similarity analysis is proposed in this paper. The spatial similarity of measurement errors is qualitatively analyzed based on the mathematical model, and quantitative analysis is presented by means of simulation and semivariogram. We then model the err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The Leica AT901-MR laser tracker is an example in this paper. Where the laser tracker measurement range accuracy is ±(10 µm + 0.5 µm/m) and the angular uncertainty is ±2 arcseconds (Zeng et al , 2020). The uncertainty of the equipment directly affects the measurement accuracy.…”
Section: Analysis Of Measurement Systems and Registration Error Factorsmentioning
confidence: 99%
“…The Leica AT901-MR laser tracker is an example in this paper. Where the laser tracker measurement range accuracy is ±(10 µm + 0.5 µm/m) and the angular uncertainty is ±2 arcseconds (Zeng et al , 2020). The uncertainty of the equipment directly affects the measurement accuracy.…”
Section: Analysis Of Measurement Systems and Registration Error Factorsmentioning
confidence: 99%
“…The importance of overcoming the problems caused by ambient temperature changes has been recognised in coordinate transformation research. Zeng et al [6] indicated that the theoretical position of measured objects would change owing to thermal expansion, and increases the error of coordinate transformation. The temperature control systems are usually deployed to maintain the temperature of assembly factories at the SRT value [7], like air conditioners, but they are costly and not practical in the assembly workshop for large and complex products.…”
Section: Introductionmentioning
confidence: 99%
“…However, the temperature field of the large-scale assembly space would become nonuniform and even shift as time goes by during the assembly process [15,16]. Zeng et al [6] found that the nonuniform temperature field could introduce extra error to the measurement process and proposed a similarity-based error compensation approach for laser tracker. Li et al [17] established a mathematical relationship between temperature change and the coordinate offset of reference points on a variable curvature workpiece with measuring the data under a nonuniform temperature field, whereas the obtained mathematical relationship is only suitable for the experimental object.…”
Section: Introductionmentioning
confidence: 99%
“…Oriented to the visual network system, whose essence is multi-vision measurement, weighted algorithms have been proposed to handle the accuracy problem [11,12]. In addition, multiple optimization methods based on the total least squares have been applied to improve registration uncertainty, which is affected by both measurement errors and configuration errors [13][14][15]. In the area of system configuration, the locations of enhanced reference points that work as a transformation basis have been thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%